1972
DOI: 10.1002/bjs.1800590907
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery in the treatment of head and neck neoplasia

Abstract: 709pressure produced as a result of rupture of the aneurysm into the tight fascia1 compartment of the psoas and iliacus muscles. The cause of the sciatic palsy was attributed to direct pressure of a common iliac artery aneurysm impinging on the nerve trunks arising from L.V.4, L.V.5, S.V.1, and S.V.2.It is interesting to speculate on the mechanism of the lateral popliteal palsy recorded in our second case. It seems unlikely that direct pressure on the nerve trunks in the pelvis can be held responsible since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

1974
1974
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 8 publications
0
3
0
4
Order By: Relevance
“…Useful applications of freezing have been reported in ear, nose and throat surgery, including the management of malignancies of the pharynx and larynx (Holden & McKelvie, 1972). Cryotonsillectomy has been satisfactorily performed by Hill (1968).…”
Section: Introductionmentioning
confidence: 99%
“…Useful applications of freezing have been reported in ear, nose and throat surgery, including the management of malignancies of the pharynx and larynx (Holden & McKelvie, 1972). Cryotonsillectomy has been satisfactorily performed by Hill (1968).…”
Section: Introductionmentioning
confidence: 99%
“…The critical determinants of the extent of cell injury in cryotherapy are the duration of freezing, the rate of freezing, the rate of thawing, and most importantly, the coldest temperature achieved 5 . Many studies have shown that temperatures of – 20°C may be lethal for cells 6–9 . Animal tissue begins to freeze at – 2.2°C 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods of treatment were described to the patients as part of the informed consent routine, but rarely was the suggested plan of treatment refused. In selection of patients with Accepted for publication May 5,1976. From the Department of Surgery, Veterans Administration Hospital and the State University of New York at Buffalo School of Medicine.…”
Section: Selection Of Patientsmentioning
confidence: 99%